2009
DOI: 10.1248/bpb.32.1422
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lansoprazole as a Novel Probe for Cytochrome P450 3A Activity by Measuring Lansoprazole Sulfone in Human Liver Microsomes

Abstract: Cytochrome P450 (CYP) 3A is the primary CYP isoenzyme subfamily responsible for phase I metabolism of Ͼ50% of drug doses administered to humans.1,2) CYP3A4 is the most prominent CYP in humans, comprising about 30% and 70% of total CYP in the liver and intestine, respectively. CYP3A has very broad substrate specificity, encompassing a wide variety of therapeutic agents.3) Many cancer chemotherapeutic agents such as vinca alkaloids, paclitaxel, irinotecan hydrochloride and other widely used drugs such as amiodar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…9,15,16) The microsomes (0.8 mg) were mixed with lansoprazole 10 mM, ethylenediaminetetraacetic acid (EDTA) 0.5 mM, Na-K phosphate 0.33 M, pH 7.4, and distilled water. The reaction was initiated by the addition of an nicotinamide adenine dinucleotide phosphate (NADPH)-generating system (MgCl 2 5 mM, NADP ϩ 0.5 mM, glucose-6-phoshate 5 mM, and 1 unit of glucose-6-phosphate 72 Vol.…”
Section: Measurement Of Lansoprazole 5-hydroxylation In Human Intestimentioning
confidence: 99%
See 2 more Smart Citations
“…9,15,16) The microsomes (0.8 mg) were mixed with lansoprazole 10 mM, ethylenediaminetetraacetic acid (EDTA) 0.5 mM, Na-K phosphate 0.33 M, pH 7.4, and distilled water. The reaction was initiated by the addition of an nicotinamide adenine dinucleotide phosphate (NADPH)-generating system (MgCl 2 5 mM, NADP ϩ 0.5 mM, glucose-6-phoshate 5 mM, and 1 unit of glucose-6-phosphate 72 Vol.…”
Section: Measurement Of Lansoprazole 5-hydroxylation In Human Intestimentioning
confidence: 99%
“…9,16) Several studies have demonstrated that the 5-hydroxylation activity of lansoprazole correlated well with the metabolic activity of the CYP2C19 probe drug mephenytoin. 15,17,18) Our studies have established the value of evaluating the activities of 5-hydroxylation and lansoprazole sulfoxidation as activities of CYP3A4 and CYP2C19 in human liver microsomes and blood samples.…”
Section: Localization Of Cyp2c19 In the Small Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…All reactions were performed according to the previously reported methods as outlined below (20,21). PHLMs (0.1 -1.0 mg) were mixed with TCL (1.0 -10.0 μM), 0.5 mM EDTA, 100 mM Na-K phosphate buffer (pH 7.4), and distilled water.…”
Section: Incubation Conditions and Extraction Substratementioning
confidence: 99%